Application of Eulerian Multi-Phase Models to Investigate Rheology of Slurries - Nadim, Nima; Javed, Mustafa (2020)
The rheology of slurries is an interesting and challenging engineering problem with enormous applications. The experimental approach is often capital-demanding and hard to interrogate and therefore the advancing CFD approaches are progressively more appealing tools. These tools need to be optimised for performance, applicability and validity. The current study evaluates the competency of Mixture and Eulerian Granular (EG) models for analysis of slurries rheological behaviour. The assessment is carried out by comparing the numerical predictions to the past published experimental reports. The case studies include dilute mixture in the pipe with an annulus cross section and dense slurry flowing through a circular pipe.